A study in cancer patients with radiotherapy assessing effectiveness of nutritional supplement and ambulation in improving fatigue and physical activity - Someshwara Rao, Pallela Narayana; Vince Vincent, Anil; Mabel, Helen (International Surgery Journal, 2020)
Background: Patients receiving radiation therapy suffer from ill effects of cancer as well as the side effects of radiation therapy. In this study, we prepared a nutritional supplement therapy and ambulation plan for the patients and assessed the improvement in physical activity and decrease in fatigue. Methods: The patients who had completed at least 3 sittings of radiotherapy in the oncology ward were selected by non-probability purposive sampling method. 60 patients were divided equally into experimental and control group. In the experiment group patients were given porridge three times a day and made to walk after drinking the porridge every day for 25 days. In both groups, post test was conducted. The data obtained was analyzed using descriptive and inferential statistics. Results: All the patients in both the groups had fatigue before the intervention. After the intervention on 30th day, 7 (23.3%) patients had mild fatigue, 23 (76.70%) had moderate fatigue and there was none with severe fatigue in the experimental group. In the control group, fatigue level became severe in 3 (10.00%) patients and remained same in others. In the experimental group, significant improvement was shown in performing physical activities after the intervention. 9 (30%) showed good physical activity, 12 (40.00%) showed moderate activity after the intervention in the experimental group. Conclusions: As there was a significant reduction in the level of fatigue and improvement in the level of physical activity in the experimental group after the intervention which could be attributed to the effect of nutritional supplement therapy and ambulation.